Arias, anthems, and chorales of the American Moravians - Kombrink, Ilona; Estanislao, Aurelio 1926-.; Johnson, Thor 1913-. (S.l. Columbia MS 6102, 1960)
Contains works by J. F. Peter, J. Herbst, J. Antes, D. M. Michael and E. W. Leinbach
Program notes on outer and inner slipcases.
Ilona Kombrink, soprano; Aurelio Estanislao, baritone; Moravian Festival Chorus and Orchtra; Thor Johnson, conductor
Keywords: Sacred vocal music; Chorales